Measuring Change in OD Panel Designs: A Response to Critics - Golembiewski, Robert T.; Billingsley, Keith R. (Academy of Management Review, 1980)
Four years ago, we reported (with Yeager) that tests utilizing survey research methods in a panel design for an organizational development (OD) project implied what we had suspected: common definitions of change are seriously inadequate. Last year, the Review published an article attacking our position [Undell & Drexler, 1979]. We respond here to their criticisms and misunderstandings.